Prediction of Reperfusion and Infarct-Related Artery Patency after Thrombolysis in Acute Anterior Myocardial Infarction by Degree of P Wave Dispersion on ECG (Bangladesh Heart Journal, 2018)
Background: The prognosis of patients with persistent occlusion of the infarct related artery (IRA), despite lytic therapy is poor. Early detection of successful reperfusion and IRA patency is of great importance in terms of prognosis and identification of candidates for rescue percutaneous coronary intervention (PCI). P wave dispersion (PWD), a new parameter measured before and after fibrinolytic therapy (FT) is supposed to predict successful reperfusion in patients with anterior acute myocardial infarction (AMI).Objectives:To examine the prediction of successful reperfusion and infarct related artery (IRA) patency by measuring P wave dispersion in 12-lead surface ECG.Method:132 patients were selected and divided into two groups on the basis of ST segment resolution (STR) after 120 minutes of thrombolysis. Group I: patients with STR >70%; Group II: patients with STR < 70%. All patients underwent coronary angiography (CAG). IRA patency was considered if TIMI flow grade was >2.Results: Mean age of the successfully thrombolysed group was 49.12±9.54 and mean age of failedthrombolysis group was 52.08±8.23 years. Though higher age was associated with failed thrombolysis and it was statistically insignificant (p=0.06). Patients with higher BMI showed no significant difference in thrombolysis. It was observed that diabetes mellitus and dyslipidemia were significantly higher in group II patients (p=0.04 and p=0.03, respectively). The mean level of PWD after 120 minutes of thrombolysis (PWD120) was statistically significant (p=0.001) between two groups. After multivariate regression analysis PWD120 was found to be the significant predictor of ST segment resolution as well as IRA patency (OR = 1.101; 95% CI = 1.012 – 1.240; p = 0.01).Conclusion: P wave dispersion (PWD) in patients receiving thrombolytic therapy can be a predictor of successful reperfusion and patent infarct related artery (IRA). PWD values, in combination with other reperfusion parameters, can contribute to the identification of rescue PCI candidates.Bangladesh Heart Journal 2017; 32(2) : 100-105